Determination of the Boltzmann constant with cylindrical acoustic gas thermometry: new and previous results combined. (11th September 2017) - Feng, X J; Zhang, J T; Lin, H; Gillis, K A; Mehl, J B; Moldover, M R; Zhang, K; Duan, Y N
Abstract: We report a new determination of the Boltzmann constant k B using a cylindrical acoustic gas thermometer. We determined the length of the copper cavity from measurements of its microwave resonance frequencies. This contrasts with our previous work (Zhang et al 2011 Int. J. Thermophys .32 1297, Lin et al 2013 Metrologia 50 417, Feng et al 2015 Metrologia 52 S343) that determined the length of a different cavity using two-color optical interferometry. In this new study, the half-widths of the acoustic resonances are closer to their theoretical values than in our previous work. Despite significant changes in resonator design and the way in which the cylinder length is determined, the value of k B is substantially unchanged. We combined this result with our four previous results to calculate a global weighted mean of our k B determinations. The calculation follows CODATA's method (Mohr and Taylor 2000 Rev. Mod. Phys .72 351) for obtaining the weighted mean value of k B that accounts for the correlations among the measured quantities in this work and in our four previous determinations of k B . The weighted mean k ^ B is 1.380 6484(28)  ×  10 −23 J K −1 with the relative standard uncertainty of 2.0  ×  10 −6 . The corresponding value of the universal gas constant is 8.314 459(17) J K −1 mol −1 with the relative standard uncertainty of 2.0  ×  10 −6 .